1998
DOI: 10.21504/sajg.v7i2.146
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and zinc status of elderly women in residential care in Cape Town

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…9,10 A local study conducted among older residents in a Cape Town old-age home found that none of the subjects had a vitamin C intake exceeding two-thirds of the RDA and that over one-third of subjects had low plasma levels (< 0.4 mg/dl) of the vitamin. 11 Vitamin C losses in vegetables prepared using a cookchill system have been studied previously, but not in South African institutions. This information would give rise to hypotheses on effective ways to minimise such losses.…”
Section: Demonstrated That 10%mentioning
confidence: 99%
“…9,10 A local study conducted among older residents in a Cape Town old-age home found that none of the subjects had a vitamin C intake exceeding two-thirds of the RDA and that over one-third of subjects had low plasma levels (< 0.4 mg/dl) of the vitamin. 11 Vitamin C losses in vegetables prepared using a cookchill system have been studied previously, but not in South African institutions. This information would give rise to hypotheses on effective ways to minimise such losses.…”
Section: Demonstrated That 10%mentioning
confidence: 99%